Description of a new species and complementary description of a known species of Iphiseiodes de Leon (Acari: Phytoseiidae) - De Carvalho Mineiro, Jeferson Luiz; De Castro, Tatiane Marie Martins Gomes [UNESP]; De Moraes, Gilberto José (Magnolia Press, 2011)
Species of Iphiseiodes De Leon have been reported only from tropical and subtropical regions of the Americas. In this paper, a new species of this genus is described from southeastern Brazil and a complementary description is provided for Iphiseiodes saopaulus (Denmark & Muma). © 2011 Magnolia Press.
Keywords: Acari; Biological control; Predatory mite; Taxonomy